Incidence of gastro-intestinal parasites in Kedah-Kelantan calves - Chandrawathani, P.; Abdullah Sani, Rehana (Veterinary Association Malaysia, 1989)
Twenty-five Kedah-Kelantan calves were monitored for one year from birth for gastrointestinal parasites. The calves were with the dams for the whole duration of the study and grazed on improved legume-based pasture. All calves were given an oral coccidiostat regularly for the first three months. Faecal examination thrice a month showed that the most common parasite was Eimeria which was present in 100 percent of the calves especially during the first six months inspite of regular coccidiostat therapy. Three species were identified; E. bovis and E. zuemii in 88 percent of the calves and E. ellipsoidalis in only two calves in the group. The next most predominant parasite was the nematode Strongyloides papillosus which was found in all the calves during the first three months. Strongyle eggs were found in 92 percent of the calves from three months onwards. Faecal culture showed that Haemonchus placei was the only strongyle present. Tapeworm (Moniezia) was noted in less than half the calves whereas Toxocara was found in only two calves in the group within the first two months. All the calves appeared to have a subclinical level of infection